Hubungan Minat Belajar Dengan Hasil Belajar Fisika Kelas XI MIPA SMA Negeri 4 Kota Jambi - Riska Fitriani; Yetri Erna (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to determine whether there is positive and significant relationship between interest in learning and physics learning outcomes for students of class XI MIPA at SMA Negeri 4 Jambi city.Methodology: This research is descriptive quantitative correlational type. The independent variable used in this study is interest in learning physics while learning outcomes are the dependent variable. The population used is students of class XI MIPA 1, XI MIPA 2, and XI MIPA 3 SMA Negeri 4 Jambi city. The sampling technique used is non-probability sampling, namely a sample with a confidence level of 90% with a sample size of 60 students. The data collection instrument used a questionnaire and test questions. Technical analysis of prerequisite test data carried out including normality test, homogeneity test, linearity test with the help of SPSS 21.Main findings: The results of hypothesis testing using the product moment correlation test with the help of SPSS 21 software at a significant level of 95% = 0.05 n = 60 obtained a Pearson correlation value of 1 means that there is a correlation between interest and learning outcomes, then H0 is rejected, this means that H1 is accepted, that is, there is a positive and significant relationship between perceptions and learning outcomes of physics students in class XI MIPA 1, XI MIPA 2, and XI MIPA 3 at SMA Negeri 4 Jambi City.Novelty of This Research: This research strengthens the relationship between interest in learning and high school physics learning outcomes.